Growth and Total Flavonoid of Three Celery (Apium graveolens L.) Varieties in Shaded Environments in The Tropical Lowland - Sari, Galuh Yunita; Aziz, Sandra Arifin; Kurniawati, Ani (Journal of Tropical Crop Science, 2022)
Celery is an introduced species of family Apiaceae from the subtropical areas. Celery leaves and stalks contain vitamins, phenolic compounds, essential oils, and other nutrients that have been used in the foods, cosmetics, and herbal industries. Shading can create a better environment for varieties adapted to the highlands to succeed to grown in the lowlands. However, the changes in the growing environment including light and temperatures might affect the flavonoid production. This study aimed to determine the growth and production of flavonoids of the highland celery varieties in the lowlands when treated with various level of shades, i.e. without shade/control, 50% shade, and 70% shade. The study used “Aroma”, a celery variety adapted to the highland, and “Summer Green”, a variety adapted to the lowland. Increases in the shade levels decrease air temperature, increases air humidity, and significantly improved the growth and production of the three celery varieties in terms of plant height, leaflets number except for the “Aroma” variety; increased leaf area, stem diameter, tiller number, crown diameter, total wet weight, total dry weight, chlorophyll a, chlorophyll b, total chlorophyll, anthocyanins, plant N (Nitrogen), P (Phosphor), K (Potassium), and total flavonoids. “Amigo” exposed to 50% shade had significantly higher flavonoids than “Aroma”. Providing shades to “Summer Green” resulted in the lower levels of flavonoids compared to without shading.